Exercise as a multitarget therapy: modulating myokines, neurotrophins, and inflammation in Parkinson’s disease - Li, Wei-Qi; Yang, Jia-Hua; Liu, Lu-Lu; Ding, Song-Tao; Yu, Bin; Jiang, Lin; Yan, Ning; Liu, Han-Deng (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease is a progressive neurodegenerative disorder characterized by degeneration of dopaminergic neurons, leading to significant motor and non-motor symptoms. Recent studies emphasize that exercise is a beneficial intervention, not only helping to decrease the risk of developing of Parkinson’s disease but also alleviating existing symptoms. This review investigates the mechanisms by which exercise influences myokines, neurotrophic factors, growth factors, and inflammation-related factors to promote neuronal survival and plasticity in Parkinson’s disease. Despite promising findings, the specific molecular pathways through which exercise exerts neuroprotective effects remain largely unexplored, and individual variability in disease progression necessitates personalized exercise interventions tailored to each patient’s needs. Furthermore, for patients unable to engage in physical activity, exploring alternative therapies that mimic exercise to achieve neuroprotective effects is crucial. In conclusion, this review highlights the need for further research to elucidate the molecular mechanisms of exercise-induced neuroprotection and to establish effective individualized exercise programs, ultimately improving the management of Parkinson’s disease.